(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the main tourist attractions of Bukhara, their historical and cultural significance, and their role in the development of tourism today. Bukhara is one of the most ancient cities in Central Asia, and its architectural monuments, madrasas, mosques, and ensembles have their own historical layers. The article discusses the history of the creation of Ark Castle, Poi-Kalon Complex, Lyabi-Hovuz Ensemble, Mir Arab Madrasa, Ulugbek Madrasa, Chor Minor Building, and other important objects, their architectural features, and the spiritual heritage transmitted through them to generations. It also analyzes the importance of these monuments in the understanding of national identity, the preservation of traditional values, and the development of international tourism. The results of the study show that cultural heritage objects are a decisive factor in increasing the tourism potential of Bukhara.